2007
DOI: 10.1016/j.socscimed.2007.02.013
|View full text |Cite
|
Sign up to set email alerts
|

The association between self-reported racial discrimination and 12-month DSM-IV mental disorders among Asian Americans nationwide

Abstract: Growing research finds that reports of discrimination are associated with mental health. However, many US studies are focused on regional samples and do not control for important confounders such as other stressors and health conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

29
332
2
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 357 publications
(365 citation statements)
references
References 66 publications
29
332
2
1
Order By: Relevance
“…For example, racial discrimination is significantly correlated with depressive symptoms in Filipino, Vietnamese, Laotian, and Cambodian eighth and ninth graders surveyed in California and Florida (Rumbaut, 1994). Similarly, racial discrimination is associated with greater risk for depressive and anxiety disorder in Vietnamese, Filipino, Chinese, Asian Indians, Japanese, Korean, and Pacific Islanders (Gee, Spencer, et al, 2007). In addition, unfair treatment related to discrimination is associated with increased prescription and illicit drug use as well as alcohol dependency in Filipino Americans (Gee, Delva, & Takeuchi, 2007).…”
Section: Racism Prejudice and Discriminationmentioning
confidence: 98%
See 2 more Smart Citations
“…For example, racial discrimination is significantly correlated with depressive symptoms in Filipino, Vietnamese, Laotian, and Cambodian eighth and ninth graders surveyed in California and Florida (Rumbaut, 1994). Similarly, racial discrimination is associated with greater risk for depressive and anxiety disorder in Vietnamese, Filipino, Chinese, Asian Indians, Japanese, Korean, and Pacific Islanders (Gee, Spencer, et al, 2007). In addition, unfair treatment related to discrimination is associated with increased prescription and illicit drug use as well as alcohol dependency in Filipino Americans (Gee, Delva, & Takeuchi, 2007).…”
Section: Racism Prejudice and Discriminationmentioning
confidence: 98%
“…Asian Americans also were denied the rights to citizenship, suffrage, and due process under the law (Zia, 2000). For example, in 1923 in United States v. Bhagat Singh Thind, the Supreme Court ruled that Asian Indians were ineligible for citizenship (Gee, Spencer, Chen, Yip, & Takeuchi, 2007). During World War II, Japanese Americans were put in internment camps and were treated as enemies (Zia, 2000).…”
Section: Racism Prejudice and Discriminationmentioning
confidence: 99%
See 1 more Smart Citation
“…These types of life events are associated with greater alcohol consumption among general populations in numerous studies, although the associations with alcohol may be mitigated by buffering factors, such as social support and coping resources (Veenstra et al, 2006) or exacerbated by poverty, racism, and other hardships (Gee, Spencer, Chen, Yip, & Takeuchi, 2007;Stockdale et al, 2007). Mulia and co-authors (2008a, b) reported that adverse experiences, such as poverty, racism, and other disadvantages, were associated with at-risk drinking and problem drinking among both minorities and whites.…”
Section: Discussionmentioning
confidence: 99%
“…Some research findings based on a nationally representative data of Asian Americans have shown a strong association between RDEs and a variety of physical and mental disorders (Gee, Spencer, Chen, Yip, & Takeuchi, 2007;Kim, Chen, & Spencer, 2012). Similarly, several studies of various Asian American ethnic groups have revealed that RDEs are strongly related to symptoms of depression (Bernstein, Park, Shin, & Park, 2011), psychological distress (Syed & Juan, 2011;Yip, Gee, & Takeuchi, 2008), heavy drinking (Kim & Spencer, 2011), alcohol and other drug use disorders (Chae, Takeuchi, Barbeau, Bennett, Lindsey, Stoddard, et al, 2008;Gee, Delva, & Takeuchi, 2007), and smoking .…”
mentioning
confidence: 99%